Community social capital or health needs: What is driving hospital-community partnerships to address social determinants of health? - Neeraj Puro; Reena Joseph Kelly (Elsevier, 2022)
Social determinants of health (SDOH) are strongly linked to individual and population health outcomes. Hospitals and health systems are in a unique position to initiate or partner on community-wide efforts address SDOH. However, such efforts typically require collaboration with other healthcare and local community organizations since SDOH affect more than just medical care. Despite studies that have identified specific organizational and environmental factors associated with hospital-community partnerships, the role of social capital and community health needs as drivers of such partnerships remains unexplored. This study examines whether hospital partnerships with community organizations in the United States are driven predominantly by community social capital or the prevailing health needs of the community, and whether these drivers are similar for overall partnerships as well as for partnerships with individual organizations. We use 2020 data from the American Hospital Association, US County Health Rankings, and Social Capital Project and employ ordinary least-squares (OLS) regression and logit models to assess the relationship between social capital, community health needs and hospital-community partnerships to address SDOH. Our results indicate that for community social capital was significantly and positively associated with total hospital partnerships (β = 0.05, p = 0.01). We also found that community social capital was significantly more likely to be associated with hospitals' partnerships with local/state public health agencies, schools, law enforcement agencies, other healthcare providers, and organizations that assist with food insecurity. On the other hand, community health needs were not associated with total partnerships and had limited associations with hospital partnerships with individual organizations. Overall, this research suggests that social capital is a critical determinant of hospital partnerships with community organizations, and hospitals may seek partnerships with organizations that allow them to address community health issues outside of their own expertise since such partnerships and collaborative efforts can help address SDOH and manage population health.